2022
DOI: 10.5671/ca.46.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Croatian and Ukrainian Anthroponymy

Abstract: In this paper, the Croatian and Ukrainian anthroponymic corpus are compared based on the twenty most common male and female names and surnames. The linguistic and cultural similarities between the Croatian and Ukrainian first name corpus are evidenced in the two most common Croatian and Ukrainian female names are Marija and Ana (Ukrainian Gana). Besides many homonymic or similar sounding modern Croatian and Ukrainian first names, the Croatian and Ukrainian first name corpora also include cognate local and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…It was reported in a study that the hyoid bone to the mandibular plane distance was longer in healthy men compared with women, and the difference notably increased as the subjects aged 39 . Various authors in their studies stated that inferiorly positioned hyoid bone to the mandibular plane leads to the constriction of posterior airway space 40–44 . Similarly, in our study, H_MNP values are significantly higher in AHI > 15 group in men and women; thus, an inferiorly positioned hyoid bone increases the severity of OSA.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was reported in a study that the hyoid bone to the mandibular plane distance was longer in healthy men compared with women, and the difference notably increased as the subjects aged 39 . Various authors in their studies stated that inferiorly positioned hyoid bone to the mandibular plane leads to the constriction of posterior airway space 40–44 . Similarly, in our study, H_MNP values are significantly higher in AHI > 15 group in men and women; thus, an inferiorly positioned hyoid bone increases the severity of OSA.…”
Section: Discussionsupporting
confidence: 74%
“…39 Various authors in their studies stated that inferiorly positioned hyoid bone to the mandibular plane leads to the constriction of posterior airway space. [40][41][42][43][44] Similarly, in our study, H_MNP values are significantly higher in AHI > 15 group in men and women; thus, an inferiorly positioned hyoid bone increases the severity of OSA. Recently, Kapsimalis F and Kryger MH reported that female patients with OSA had a shorter soft palate than the male patients with OSA and H_MNP was abnormal in both male and female patients with OSA similarly.…”
Section: Ta B L E 4 (Continued)supporting
confidence: 79%
“…In the present study, the only cephalometric parameter found to be statistically significant was the posterior facial height (S-Go). This is consistent with findings from other studies, such as those by Ryu et al (2015) 32 and Vidovic et al ( 2013) 33 . In addition to confirming the above findings, a study by Woodson et al (1997) 34 revealed that an increase in posterior facial height is associated with a worse therapeutic response to uvulopalatopharyngoplasty.…”
supporting
confidence: 94%
“…OSAS-specific symptoms, such as mandibular retrognathia, mandibular micrognathia, increased values of the ANB angle(angle between lines NA and NB), lower position of the hyoid bone, and decrease in upper and lower pharynx space are cephalometric measures that have shown a greater association with the diagnosis of OSAS. Despite the above, the craniofacial features associated with OSAS vary across populations and ethnic groups [11,12].…”
Section: Introductionmentioning
confidence: 99%